Global trends and challenges in water science, research and management - Zainudin, Zaki; Koning, Wendell; Weyand, Michael; Kelderman, Peter; Crabtree, Bob (International Water Association, 2012)
Leaps and bounds have been made in areas related to river basin management on a global scale, inline with various technological advances of the 21st century. This chapter reviews 6 emerging trends related to water science, research and management.